IMPLEMENTATION OF ARTIFICIAL INTELLIGENCE IN THE EDUCATIONAL PROCESS OF COMPUTER SCIENCE MASTER’S STUDENTS - Otroshko, Tamara; Shkola, Olena; Kalinichenko, Oleksandr (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2024)
The article is dedicated to a careful consideration of the impact of artificial intelligence on the educational process of master’s students in computer science, in particular its role in ensuring the quality of education, solving complex tasks and training future specialists. Based on the analysis of this topic, it is possible to better understand the potential of AI and determine the best practices for its successful implementation in the educational process. Artificial intelligence is the main innovation of the 21st century, which promotes the possibility of creating new sites for conquest, managing the process of making new decisions. They allow to fully create and implement an active process of creating a higher level.